Whiteness: influence, decision-making, and cultural-linguistic disproportionality in special education placements - Steen, Leonard H., II (Kansas State University, 2022)
Disproportionate representation of culturally-linguistically diverse (CLD) students in special education has been well documented. Existing research has largely focused on the attitudes and beliefs of classroom teachers and the processes that lead to these placements. Few studies have examined how the perspectives of child study team (CST) members contribute to placements in special education. CSTs are involved in interventions, referrals, evaluations, and placement decisions. The purpose of this study was to identify how unspoken epistemological, sociolinguistic, and psychological perspectives rooted in the dominant White culture explain their actions and decision making. Data sources included observations of meetings, written record reviews, and individual semi-structured interviews. Qualitative data gained from these sources were analyzed to identify themes in CST members’ discourse which were then compared to perspectives based in Whiteness. Results indicated participants felt an urgency to evaluate to provide students support, focusing on completeness, not quality, of intervention data. Once referred, intervention data and student background information were ignored in favor of standardized evaluations. Data in conflict with quantitative measures were dismissed and parent input was disregarded with criticisms of their abilities. Findings were consistent with the dominant culture’s beliefs in meritocracy and its perceived neutrality or universality, and disregard for contradictory data sources may reflect resistance to challenges to these beliefs. The perspectives rooted in the dominant culture held by CST members may explain their actions and decision making with CLD students that lead to inappropriate referrals to and placements in special education. More research is needed to determine how directly addressing these perspectives can influence outcomes for CLD students.
Keywords: Whiteness; Cultural-linguistic diversity; Disproportionality; Special education evaluation; Child study teams